A simple correlation for predicting the rise time of fire-induced smoke flow in a tunnel with longitudinal ventilation. (April 2020) - Tao, Haowen; Xu, Zhisheng; He, Lu; Liu, Qiulin; Zhao, Jiaming; Luan, Dia; Fan, Chuangang; Gong, Chenjie
Highlights: Theoretical analysis was provided concerning the rise time of smoke flow in tunnel. The rise time of smoke flow would be larger in the presence of longitudinal wind. Correlations for predicting the rise time of smoke flow have been newly proposed. Abstract: The rise time of the smoke flow fronts is an important parameter for fire detection. However, very limited literatures, if not none, have been available to report the predictive correlation or data for the rise time of fire-induced smoke flow in a longitudinally ventilated tunnel. In this study, theoretical analyses were conducted to deduce a simple mathematical correlation considering the effect of longitudinal crosswind disturbance. Computational fluid dynamics (CFD) with large eddy simulation (LES) method was performed to simulate the rising smoke flow with various heat release rates, source-ceiling heights, and wind velocities. The results show that the rise time of smoke flow in the presence of longitudinal crosswind was much larger than that in the absence of longitudinal crosswind, which may be attributed to the enhanced air entrainment that decelerated the rising smoke flow. The numerical results then served as the validation data for the proposed correlation, which confirmed that the smoke flow rise time varied as the −1/2 power of the convective heat release rate, 1/2 power of the ambient wind velocity, and 4/3 power of the height above the fire source. The proposed correlation was found to be capable of predicting the rise time of smoke flow in both windy and windless environments. The findings of this paper contribute to an improved understanding of rising smoke propagation in the tunnel under windy condition. It would also be beneficial to the design of fire detection system for the longitudinally ventilated tunnels.